Green HRM Practices To Enhance Environmental Performance Through Green Innovation In The Regional Secretariat Employees of Pasuruan City Government - Adam Maulana; Amiartuti Kusmaningtyas; Siti Mujanah (Journal of Social Research, 2025)
The research problem focuses on the gap between the formulated Green policies and their uneven implementation Practices in the Regional Secretariat of Pasuruan City Government. This includes the lack of optimization in the application of Green Human Resource Management (GHRM) and Green Innovation, which affects the effectiveness of improving environmental performance in a sustainable manner in the organization. The research method used in this research is explanatory research with a quantitative approach, the number of samples used is 150 respondents, the data collection technique used only uses a survey with an instrument through a questionnaire. The analysis technique used is descriptive analysis, and SEM-PLS analysis with mediation effects. The testing tool used is the Smart-PLS version 3.3 application. The results of this study indicate that the overall significance value in this study shows less than 0.05. This means that partially there is an influence of Green Human Resource Management (GHRM) Practises (X), and Green Innovation (Z). on Environmental Performance (Y), and based on the mediation analysis shows that Green Human Resource Management (GHRM) Practises through Green Innovation has a significant effect on Environmental Performance in Pasuruan City Government Regional Secretariat Employees. For future research, it is recommended to refine the measurement of GHRM with more specific indicators, expand the scope of research to various sectors, and conduct longitudinal studies to observe long-term impacts. Additionally, strengthening collaborations with academic institutions to integrate the latest innovations and methodologies in research is encouraged